Analisis Penanggulangan Banjir Dan Kesiapsiagaan Dalam Mitigasi Banjir Kampung Baru Kecamatan Medan Maimun - Khairunnisa Effendi; Khairiyah Dwie Vanesa; Elva Hariyani; Aina Fitrah Aulia Ritonga; Siregar, Muthia Afrah Goslan; Putra Apriadi Siregar (Journal of Educational Innovation and Public Health, 2023)
Flooding is a problem that still requires special attention from a number of parties, including the community and the government. Flooding is not a light matter. Flooding can occur due to rising water levels due to above-average rainfall, temperature changes, levees or dams bursting, or obstruction of water flow elsewhere. The lack of community management and preparedness for disasters is one of the causes of the high impact of post-disaster damage or loss, so disaster mitigation is needed as an effort to reduce disaster risk. The research aims to analyze public knowledge about flood mitigation and preparedness. This study used qualitative research methods with the sampling technique used was simple random sampling. It was found that among several questions in the interview that the author asked about flood management knowledge and preparedness in flood disaster mitigation, all informants responded and acted very well. From the research conducted, all informants expect attention from the government to make improvements to the drainage system again and make new drainage. And the author hopes that the arrangement of residential areas on the banks of the river will be carried out to overcome floods that often hit the Kampung Baru area, Medan Maimun District.